2017
DOI: 10.1007/164_2016_119
|View full text |Cite
|
Sign up to set email alerts
|

Gastrointestinal Pharmacology

Abstract: Little data support the use of most medications commonly used to treat FAPDs in children. More randomized, placebo-controlled studies are needed to assess the efficacy of pharmacological interventions in the treatment of FAPDs in children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 143 publications
2
21
0
Order By: Relevance
“…After 2 weeks, 75% of children receiving peppermint oil reported reduced pain intensity compared with the placebo group, although none of the antispasmodics routinely used in clinical practice in the USA was studied. Trimebutine is an opioid agonist that induces the release of motilin (which controls the pattern of smooth muscle cell contraction) and modulates the release of vasoactive intestinal peptide, glucagon and gastrin 197 . An RCT found trimebutine to be effective in relieving pain in children with IBS 197,198 (TABle 1).…”
Section: Pharmacological Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…After 2 weeks, 75% of children receiving peppermint oil reported reduced pain intensity compared with the placebo group, although none of the antispasmodics routinely used in clinical practice in the USA was studied. Trimebutine is an opioid agonist that induces the release of motilin (which controls the pattern of smooth muscle cell contraction) and modulates the release of vasoactive intestinal peptide, glucagon and gastrin 197 . An RCT found trimebutine to be effective in relieving pain in children with IBS 197,198 (TABle 1).…”
Section: Pharmacological Therapymentioning
confidence: 99%
“…Trimebutine is an opioid agonist that induces the release of motilin (which controls the pattern of smooth muscle cell contraction) and modulates the release of vasoactive intestinal peptide, glucagon and gastrin 197 . An RCT found trimebutine to be effective in relieving pain in children with IBS 197,198 (TABle 1). Additionally, a double-blind placebo-controlled trial in children with FAP-NOS showed significant benefit with the use of mebevirine (an anticholinergic agent that relaxes the intestinal smooth muscles and decreases peristalses) on pain compared with placebo 199 .…”
Section: Pharmacological Therapymentioning
confidence: 99%
“…FAPDs [ 20 ] define a group of FGIDs with pain as the driving symptom. Within this group, four subgroups have been defined: Irritable bowel syndrome (IBS), functional dyspepsia, functional abdominal pain-not otherwise specified (FAP-NOS), and abdominal migraine [ 71 ] with the first three diagnostic categories being more prevalent than the latter.…”
Section: Functional Abdominal Pain/irritable Bowel Syndromementioning
confidence: 99%
“…Although many clinicians rely on the pharmacological approach, the overall efficacy of pharmacological agents in IBS is low. Several systematic reviews have pointed out the lack of well-designed high quality clinical trials in this area and lack of therapeutic efficacy of these agents[ 204 , 205 ]. The other issue pertaining to the clinical trials in children with FAPDs is that almost all paediatric trials have lumped together all FAPDs rather than including one specific FAPD such as IBS or FD.…”
Section: Management Of Ibsmentioning
confidence: 99%
“…Rifaximin elicits its antimicrobial properties by binding to the beta-subunit of the bacterial DNA-dependent RNA polymerase and thus inhibiting bacterial RNA syn283 synthesis. It has been approved for the treatment of IBS-D in adults[ 204 ].…”
Section: Management Of Ibsmentioning
confidence: 99%